An Empirical Analysis of the Structuration of American Ideologies About Economic Justice - Holland, Curtis (Qualitative Sociology Review, 2013)
A consensus has been forming among structural social psychologists that most Americans hold beliefs in both individualistic and structural explanations of inequality. Yet, even many who espouse structural beliefs nonetheless emphasize individual-level explanations of inequality to disproportionate extents. This study is aimed to identify common trends in the logic used by a conventional group of Americans – MBA students – to rationalize their more general political and economic beliefs. While a large number of studies have emphasized the prevalence of dominant ideology beliefs, and others have speculated theoretically on how such beliefs are reproduced, this study aims to bring these bodies of work together. I sought to build an initial understanding of how contradictions in Americans’ political and economic ideologies are transmuted, and to identify heuristic concepts fundamental to this process. Findings suggest that particular assumptions about human nature serve to “fill” the cognitive “gap” which would otherwise present individuals with insurmountable ambiguities in their ideologies about economic justice. Respondents also reflected some level of awareness of the impact of ideology on their thought processes, even as they accept such processes, and the realities they constitute, as inevitable.